ORGANIZATIONAL LEARNING, ACADEMIC SUPERVISION, AND WORK MOTIVATION IN ENHANCING TEACHING COMPETENCE AND TEACHER PERFORMANCE IN MODERN PESANTREN - Abdu Alifah; Anggraini Sukmawati (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2021)
Abstract: Teaching competence and teacher performance are determinant issues in Islamic educational institutions to date, including modern pesantren. Therefore, this study attempted to analyze the effect of organizational learning, academic supervision, and work motivation that possibly enhance teaching competence and teacher performance which has been rarely studied, especially in pesantren. This study involved 128 teachers at modern pesantren Ummul Quro Al-Islami Bogor selected through a simple random sampling method. The collected data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results found that teaching competence positively and significantly affected teacher performance in modern pesantren. Furthermore, organizational learning was also found to positively and significantly affect teaching competence and teacher performance. Meanwhile, academic supervision and work motivation positively and significantly affected teaching competence, but insignificantly affected teacher performance. This study also examined the indirect effect and found that organizational learning, academic supervision, and work motivation positively and significantly affected teacher performance in modern pesantren mediated by teaching competencies. Thus, modern pesantren can effectively enhance their teachers' performance by increasing organizational learning, academic supervision, and work motivation through the mediation of teaching competencies. Keywords: organizational learning; academic supervision; work motivation; teaching competence; teacher performance